Dinamika Khulu’ dan Peran Pengadilan Agama Sidoarjo: Analisis Peningkatan Perkara Cerai Gugat Pasca-COVID-19 - Lutfi Soleh AM, Khusnul; Zakki, Muhammad; Huda, Misbahul (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
The COVID-19 pandemic was expected to impact not only the economic and health aspects of society but also potentially affect social dynamics and household stability, including an increase in divorce cases. However, the reality shows a significant surge in divorce cases, particularly khulu', at the Sidoarjo Religious Court following the pandemic. This phenomenon marks a significant change in divorce patterns occurring after the COVID-19 period, warranting further investigation to understand the causes and potential solutions. This study aims to analyze the dynamics of khulu', identify factors influencing the rise in divorce cases, and evaluate the role of the Sidoarjo Religious Court in addressing and reducing divorce cases. The research is field-based with a qualitative approach. The methodology used is a case study with descriptive analysis. The results indicate that the dynamics of khulu' in Sidoarjo have undergone significant changes, with an increase in divorce cases during the post-COVID-19 period. Factors such as economic pressure, changes in social interaction patterns, and emotional instability have triggered this surge. To minimize the prevalence of khulu' and divorce, the Sidoarjo Religious Court focuses on strengthening mediation, public education, rationalizing administrative requirements, and assisting families in resolving conflicts peacefully.